2001
DOI: 10.19182/remvt.9790
|View full text |Cite
|
Sign up to set email alerts
|

Prévalence de la cysticercose porcine dans le Mayo-Danay (Nord Cameroun) et le Mayo-Kebbi (sud-ouest du Tchad)

Abstract: Une étude menée de mai à octobre 1999 dans le département du Mayo- Danay (extrême nord du Cameroun) et dans la préfecture du Mayo-Kebbi (sud-ouest du Tchad) a eu pour but de déterminer la prévalence de la cysticercose porcine et d’identifier les principaux facteurs qui la favorisaient. Elle a montré que les conditions hygiéniques dans lesquelles vivait la population ainsi que celles de l’élevage des porcs étaient très médiocres, avec pour conséquence des infestations massives de la population porcine par des c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…However, what many of these studies seem to agree upon is the high prevalence of T. solium cysticercosis in porcine farming and pork eating populations. This relationship has been systematically reported in various studies on Cameroon and Africa Assana et al, 2001;Shey-Njila et al, 2003;Nguekam et al, 2003;Thomas et al, 2016;Vondou et al, 2002). Incidentally, epilepsy prevalence is also generally higher in areas associated with high rates of porcine farming.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…However, what many of these studies seem to agree upon is the high prevalence of T. solium cysticercosis in porcine farming and pork eating populations. This relationship has been systematically reported in various studies on Cameroon and Africa Assana et al, 2001;Shey-Njila et al, 2003;Nguekam et al, 2003;Thomas et al, 2016;Vondou et al, 2002). Incidentally, epilepsy prevalence is also generally higher in areas associated with high rates of porcine farming.…”
Section: Discussionsupporting
confidence: 62%
“…Surveys across Cameroon have demonstrated the strong relationship between porcine farming and cystercecorsis Assana et al, 2001;Prouedet et al, 2002;Shey-Njila et al, 2003). The intensity of this relationship is determined by local hygiene, sanitation and sociocultural factors like feeding pigs by defecating directly into their pens, weak technical capacity to detect and treat T. solium carriers, inadequate meat inspection and the consumption of poorly cooked pork.…”
Section: Patternmentioning
confidence: 99%
“…The latter practice has also been reported to be common in the West province of Cameroon (Marty et al, 1986;Zoli et al, 1987;Pouedet et al, 2002). However, this is not the case in the Far North of Cameroon, where inhabitants are in the habit of defecating near the farms in the open air and where pigs scavenge the human excrement (Assana et al, 2001). In Batibo sub-division, the local authorities obliged the inhabitants to construct latrines.…”
Section: Discussionmentioning
confidence: 99%
“…The T. solium taeniasis/cysticercosis complex is associated with poor sanitation and hygiene, poor methods of pig husbandry and poor meat inspection and control. The occurrence of the taeniasis /cysticercosis complex has been reported already in some parts of Cameroon (Marty et al, 1985(Marty et al, , 1986Zoli et al, 1987;Awa et al, 1999;Assana et al, 2001;Pouedet et al, 2002). In order to obtain baseline data on the prevalence of porcine cysticercosis in the North-West province of Cameroon and to determine factors associated with the transmission of this zoonosis, an epidemiological study was undertaken in the Batibo sub-division of this province.…”
Section: Introductionmentioning
confidence: 99%
“…16 In addition, the TSOL18 antigen was shown to completely eliminate transmission of T. solium to pigs in a vaccine field trial conducted in the Mayo-Danay district of north Cameroon, 17 a region previously identified as having a high prevalence of T. solium. 18,19 A second, more recent vaccine field trial was undertaken in rural villages in the Morropon province of north-east Peru, 8 and again vaccination greatly reduced the total number of parasite cysts in immunized pigs (99.7% reduction compared with control pigs). incomplete reverse transcription during cDNA library construction.…”
mentioning
confidence: 99%